Kondisi Psikologis Lansia Yang Depresi Dan Upaya Penanganannya Di UPTD Rumoh Seujahtra Geunaseh Sayang Ulee Kareng Banda Aceh - Maula Arifa; Abu Bakar; Nurbaity Bustamam (JIMBK: Jurnal Ilmiah Mahasiswa Bimbingan & Konseling, 2018)
ABSTRACTElderly or elderly are age groups or in humans who have entered the final stages of all phases of life. These elderly people desperately need a great attention from the family environment and also the environment to avoid the occurrence of depression. This study aims to (1) to find out the depictions of psychological condition of elderly depression in UPTD Geunaseh darling Ulee Kareng Banda Aceh; and (2) to know the handling efforts provided to assist the psychological condition of the depressed elderly in UPTD Geunaseh Sayang Ulee Kareng Banda Aceh. The method used in this research is survey method with qualitative approach. The collection of respondents was determined by using puspose sampling technique. Respondents in this study amounted to 4 elderly people with female gender who have symptoms of depression with age range 65-78 years. Collecting all data was done by interview using questioner and observation directly at research location. Data analysis used in this research is descriptive analysis. To measure the level of elderly depression is by using Geriatric Depression Scale (GDS). The result of data analysis obtained that the psychology condition of elderly are at light and moderate level. Attempts for handling for the elderly have been given at this time that is with the experts experts such as psychologists, doctors, nurses and Ustadz / Ustadzah. Experts here play a role to deal with problems experienced by the elderly according to their respective expertise.